Management of Verticillium Wilt of Potato with Disease-Suppressive Green Manures and as Affected by Previous Cropping History - Larkin, Robert P (Plant disease, 2011)
The ability of disease-suppressive rotation crops to reduce potato disease problems and increase crop productivity in a field with prior severe Verticillium wilt, as well as the potential influence of previous cropping history on disease suppression, was evaluated over three field seasons in Maine. Disease-suppressive rotations consisted of: (i) a high-glucosinolate mustard blend ('Caliente 119') as a mixture of white mustard (Sinapis alba) and oriental mustard (Brassica juncea) with known biofumigation potential and (ii) a sorghum-sudangrass hybrid. Each were grown as single-season green manures followed by a subsequent potato crop. These rotations were compared with a standard barley rotation and a barley rotation followed by chemical fumigation with metam sodium as controls. Both green manure rotations significantly reduced (average reductions of 25 and 18%, respectively) Verticillium wilt in the subsequent potato crop compared with the standard barley control but were not as effective as chemical fumigation (35% reduction). The mustard blend also reduced other soilborne diseases (black scurf and common scab) better than all other rotations. Mustard blend and chemical fumigation treatments increased tuber yield relative to the barley control by 12 and 18%, respectively. However, by the second rotation cycle, disease levels were high in all rotations, and only chemical fumigation resulted in substantial disease reduction (35%). Rotations also had significant effects on soil microbiology, including soil bacterial and fungal populations and microbial community characteristics based on fatty acid profiles. However, only chemical fumigation significantly reduced soil populations of Verticillium spp. and increased general soil microbial activity. Previous cropping history did not significantly affect disease reduction, tuber yield, or soil microbial communities. This research indicates the potential for using disease-suppressive rotations for managing Verticillium wilt and other soilborne diseases but also indicates that multiple years of disease-suppressive crops may be needed to substantially reduce disease in heavily infested fields